2016
DOI: 10.4238/gmr15048179
|View full text |Cite
|
Sign up to set email alerts
|

Management of clinically negative nodes (N0) in supraglottic laryngeal carcinoma: A systematic review

Abstract: ABSTRACT. The purpose of this study was to evaluate the treatment of clinically negative cervical lymph nodes in supraglottic carcinoma by a meta-analysis. The search words were "supraglottic carcinoma", "cervical lymph nodes negative/cN0", "radical neck dissection", and "radiotherapy". The databases included the Chinese biomedical literature database, Medline, Cochrane library, EMBASE database, journals, and theses, etc. from 1989 onwards. Using the 5-year overall survival, disease-free survival, and disease-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…In the current study, surgery yielded better survival than radiotherapy in patients with T1a stage glottis SCC, but not T1b, T1 not specified, or T2 stages. Our analysis showed that there is no statistically significant association between the mode of treatment and survival of early‐stage supra‐ and subglottic SCC, which is consistent with a previous report . The number of patients with T1‐2N0M0 subglottic cancer in our study was limited, perhaps because the vast majority of patients with subglottic cancer present with a locally advanced stage…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, surgery yielded better survival than radiotherapy in patients with T1a stage glottis SCC, but not T1b, T1 not specified, or T2 stages. Our analysis showed that there is no statistically significant association between the mode of treatment and survival of early‐stage supra‐ and subglottic SCC, which is consistent with a previous report . The number of patients with T1‐2N0M0 subglottic cancer in our study was limited, perhaps because the vast majority of patients with subglottic cancer present with a locally advanced stage…”
Section: Discussionsupporting
confidence: 88%
“…The overall metastatic rate of cN0 patients was greater than 20% in pathologic examination (21,22,24), while the LMRs of contralateral levels II to III were relatively low in types A and B groups in our study. IM was detected in levels II and III with LMRs of 21 and 11.1%, respectively, while CM was detected in 6.3 and 4.8%, respectively.…”
Section: Discussioncontrasting
confidence: 51%
“…This result was in accord with the biological behavior of malignancies. Poorly differentiated cells possess a greater capacity to invade lymphatic vascular spaces, which enable tumor cells to enter the bloodstream and lymphatic channels and disseminate widely in the body (24), indicating that poor differentiation should be considered when we design CTV delineation.…”
Section: Discussionmentioning
confidence: 99%
“…5 Regarding the management of cervical lymph nodes in cN0 SC, one research group reported that neck dissection did not improve patients' survival rates but led to overtreatment of 70%-100% of patients and increased the treatmentrelated complications, hospitalization time, and costs. [5][6][7] However, another report suggested that occult metastases may develop into clinical lymph node metastases, and that patients may require a second operation; therefore, selective neck dissection should be performed with surgery. 8 Although most studies showed that lymph node dissection (LND) should be performed in cN0 SC patients, the SC cohorts in these studies constituted stage T1-4, and not exclusively classification T1-2.…”
Section: Introductionmentioning
confidence: 99%